Implementasi Sila Ketiga Pancasila Dalam Menyikapi Keberagaman - Arsalan, Akmal; Gultom, Berlian; Fajrin, Muhammad Defa Ilham Nur (Tumoutou Social Science Journal, 2025)
The background of this study is about the implementation of the values of the third precept of Pancasila in exploring the diversity that exists in Pamulang University students. PPKn students as prospective educators have a responsibility to instill Pancasila values in future generations. Diversity in the campus environment often creates unique social dynamics. Students from various backgrounds interact and collaborate in a variety of academic and non-academic activities. The purpose of this research is to produce writings that focus on certain topics or issues and support individual research projects. The method used is a literature review method which is the first and essential step in research planning. that the differences that exist around our living environment must coexist and respect each other. There is no sense of superiority so as to degrade others, no feeling better so as not to demonize the others, and not feel more important than others.